Muscle Afferent Receptors Engaged in Augmented Sympathetic Responsiveness in Peripheral Artery Disease - Li, Jianhua; Xing, Jihong (Frontiers in Physiology, 2012)
The exercise pressor reflex (EPR) is a neural control mechanism responsible for the cardiovascular responses to exercise. As exercise is initiated, thin fiber muscle afferent nerves are activated by mechanical and metabolic stimuli arising in the contracting muscles. This leads to reflex increases in arterial blood pressure (BP) and heart rate primarily through activation of sympathetic nerve activity (SNA). Studies of humans and animals have indicated that the EPR is exaggerated in a number of cardiovascular diseases. For the last several years, studies have specifically employed a rodent model to examine the mechanisms at receptor and cellular levels by which responses of SNA and BP to static exercise are heightened in peripheral artery disease (PAD), one of the most common cardiovascular disorders. A rat model of this disease has well been established. Specifically, femoral artery occlusion is used to study intermittent claudication that is observed in human PAD. The receptors on thin fiber muscle afferents that are engaged in this disease include transient receptor potential vanilloid type 1 (TRPV1), purinergic P2X, and acid sensing ion channel (ASIC). The role played by nerve growth factor in regulating those sensory receptors in the processing of amplified EPR was also investigated. The purpose of this review is to focus on a theme namely that PAD accentuates autonomic reflex responses to exercise and further address regulatory mechanisms leading to abnormal sympathetic responsiveness. This review will present some of recent results in regard with several receptors in muscle sensory neurons in contribution to augmented autonomic reflex responses in PAD. Review of the findings from recent studies would lead to a better understanding in integrated processing of sympathetic nervous system in PAD.